Case Study: United States Agency for International Development (USAID) investment in innovation for sustainable agricultural intensification - Dalberg Asia (Commission on Sustainable Agriculture Intensification, 2021)
USAID has played a crucial role in shaping global shifts in agriculture and sustainable agricultural intensification (SAI) through the decades. The agency has constantly fostered agricultural innovation - from the Green Revolution in the 1960s to the market-economy transition in the 1990s1 . USAID’s more recent work has followed the priorities of the Feed the Future (FTF) initiative, the US government's flagship global hunger and food security initiative. Furthermore, the FTF innovation laboratories have played a key role in setting up definitions and furthering the global discourse on SAI. This case study explores the investments made by USAID in agriculture innovation overall as well as SAI innovation over the last decade.